Anti-inflammatory activity of herb products from Licania rigida Benth. (August 2019) - Santos, Enaide Soares; de Morais Oliveira, Cícera Datiane; Alencar Menezes, Irwin Rose; do Nascimento, Emmily Petícia; Correia, Denise Bezerra; de Alencar, Cícero Damon Carvalho; de Fátima Sousa, Maria; Fernandes Lima, Cícera Norma; Monteiro, Álefe Brito; de Souza, Camila Pedroso Estevam; de Araújo Delmondes, Gyllyandeson; Bezerra, Daniel Souza; et al.
Highlights: The extract is rich in phenolic compounds and flavonoids. The extract presented an anti-inflammatory effect, affecting the metabolic route of arachidonic acid. The extract showed a reduction in leukocyte migration, indicating an inhibition of cytokine production. Abstract: Purpose: The objective of the present study was to evaluate the systemic anti-inflammatory activity of the hydroalcoholic extract of the leaves of Licania rigida Benth (EHFLR) on models of systemic inflammation in mice. Methods: The quantitative chemical profiles of phenolic acids and flavonoids were performed by High-Performance Liquid Chromatography (HPLC). Systemic anti-inflammatory activity was determined from carrageenan and dextran-induced paw edema models and the animals were orally treated (p.o.) with EHFLR at doses of 25, 50, 100 mg/kg, indomethacin (10 mg/kg) for carrageenan-induced paw edema and promethazine (6 mg/kg) for dextran-induced paw edema. The possible mechanisms involved in the anti-inflammatory action of the extract were evaluated by the paw edema models induced by histamine and arachidonic acid, and by the model of carrageenan-induced peritonitis, where vascular permeability and leukocyte migration to the peritoneal cavity were evaluated. Results: The results of the HPLC identified the presence of phenolic acids and flavonoids, with chlorogenic acid (1.16%) and Caempferol (0.81%) as the main constituents. From the results, it was concluded that the extract has an LD50 ≥5000 mg/kg when administered orally in mice as this dose did not trigger deaths in any of the observed groups. EHFLR (25 mg/kg) showed a significant antiderematogenic effect on histamine and arachidonic acid-induced paw edema at the third hour of the tests, with a percentage of inhibition of 46.64% and 18.33%, respectively. The extract (25 mg/kg, p.o.) also significantly reduced vascular permeability and leukocyte migration in the peritoneal cavity. Conclusions: It is concluded that EHFLR exerts a systemic anti-inflammatory action, which seems to depend, at least in part, on the inhibition of arachidonic acid metabolism and the action of vasoactive amines. In addition, the extract reduced the leukocyte migration in the peritoneal cavity, indicating that its action may be linked to the inhibition of pro-inflammatory cytokines.